Corpus-based analysis of the usage pattern of homonymys among malaysian ESL learners - Law, Hui Qin (2022)
Learners usually deal with words that have multiple meanings, and similar pronunciation and spelling when they acquire English vocabulary. These words are homonyms that often confuse learners due to their ambiguous nature, similarity in orthography and pronunciation. Most learners faced difficulties distinguishing several types of homonyms and knowing the usage of homonyms in different contexts. This study analyses the types and usage patterns of the homonyms used by Malaysian undergraduates in their essay writing. The study adopted a corpus-based method to conduct the research, and a total of 145 essays were collected and digitised to generate a learner corpus. In the learner corpus, there are 8098 homonyms found and classified into homophones, homographs, lexical homonyms, and lexico-grammatical homonyms. The usage patterns of homonyms are examined through common usage, misuse pattern, and collocational pattern based on different homonym categories. The result showed that the word classes of most homonyms determined the word sense used in a particular context, except for lexical homonyms. Apart from grammatical class, context also played a significant role in disambiguating multiple senses of homonyms. Based on the usage patterns, learners experienced biases, confusion, L1 interference, and misunderstand senses of homonyms while building sentences. The corpus highlighted grammatical class, meanings, and context are the key elements used to address these issues. This paper concluded that corpus could be a practical tool to learn several homonym categories and their usage in different contexts.